Venous thromboembolism during pregnancy or postpartum: Findings from the RIETE Registry - Blanco-Molina, Angeles; Trujillo-Santos, Javier; Criado, Juan; Lopez, Luciano; Lecumberri, Ramón; Gutierrez, Reyes; Monreal, Manuel; for the RIETE Investigators (Thrombosis and Haemostasis, 2007)
Venous thromboembolism (VTE) occurs infrequently during pregnancy, and issues concerning its natural history, prevention and therapy remain unresolved. RIETE is an ongoing registry of consecutive patients with objectively confirmed, symptomatic acute VTE. In this analysis, we compared the clinical characteristics and outcome for all enrolled pregnant and postpartum women with acuteVTE, and all non-pregnant women in the same age range. Up to May 2005, 11,630 patients were enrolled in RIETE, of whom 848 (7.3%) were women aged < 47 years. Of them, 72 (8.5%) were pregnant, 64 (7.5%) postpartum. Pregnant women presented less often with symptomatic pulmonary embolism (11%) than non-pregnant women (39%). VTE developed during the first trimester in 29 (40%) pregnant patients; in the second in 13; in the third in 30. Thrombophilia tests were m Venous thromboembolism (VTE) occurs infrequently during pregnancy, and issues concerning its natural history, prevention and therapy remain unresolved. RIETE is an ongoing registry of consecutive patients with objectively confirmed, symptomatic acute VTE. In this analysis, we compared the clinical characteristics and outcome for all enrolled pregnant and postpartum women with acuteVTE, and all non-pregnant women in the same age range. Up to May 2005, 11,630 patients were enrolled in RIETE, of whom 848 (7.3%) were women aged < 47 years. Of them, 72 (8.5%) were pregnant, 64 (7.5%) postpartum. Pregnant women presented less often with symptomatic pulmonary embolism (11%) than non-pregnant women (39%). VTE developed during the first trimester in 29 (40%) pregnant patients; in the second in 13; in the third in 30. Thrombophilia tests were m
Keywords: Venous thromboembolism; prophylaxis; pregnancy